A Ugandan Parenting Programme to Prevent Gender-Based Violence: Description and Formative Evaluation. (May 2022) - Wight, Daniel; Sekiwunga, Richard; Namutebi, Carol; Zalwango, Flavia; Siu, Godfrey E.
Purpose : To develop a culturally-sensitive intervention for the early prevention of gender-based violence (GBV) in Uganda.Methods : Programme design followed the 6SQuID model of intervention development and multi-sectorial advice. A formative evaluation was conducted in two communities with six groups and 138 participants.Findings : Four familial predictors of GBV were identified as potentially malleable: poor parent–child attachment, harsh parenting, inequitable gendered socialization and parental conflict. A community-based parenting programme was developed to address them. Its programme theory incorporates Attachment Theory, the concept that positive behavioural control develops emotional control, and Social Learning Theory. Its rationale, structure and content are presented using the TIDieR checklist. A formative evaluation showed the programme to be widely acceptable, culturally appropriate, and perceived to be effective, but also identified challenges.Conclusion : The careful development of this community-based parenting programme shows promise for the early prevention of GBV.